Evaluation of Anticancerous and Immunomodulatory Potentials of Thuja occidentalis - Verma, Satish Kumar; Singh, Santosh Kumar (Indian Forester, 2012)
Anticancerous and immunomodulatory properties of Thuja occidentalis extracts were analyzed that showed varied responses. In vitro cytotoxicity (performed by standard SRB assay) was observed against the liver (hep-2) and colon (HT-15) human cancer cell lines. The intraperitoneal injection of methanolic extract (240 mg/kg body weight in Swiss mice), proved to be effective against induced Ehrlich Ascitic Carcinoma. Methanolic extract effectively decreased the cancer cell line counts in peritoneal fluid of EAC mice than the normal control groups of mice. A significant increase in humoral and cell mediated response was observed at high doses of methanolic extract of Thuja occidentalis. Significant alterations in the WBC/RBC count in Ehrlich Ascitic carcinomas bearing mice were observed.